1978
DOI: 10.1007/bf00235805
|View full text |Cite
|
Sign up to set email alerts
|

Selective degeneration of two out of the nine types of synapses in cat caudate nucleus after cortical lesions

Abstract: In the cat caudate nucleus the same nine types of synapses are found as in putamen and fundus striati. The three parts of the striatum in the strict sense do not differ in the morphological differentiation of synapse types but only in their quantitative distribution. One-third of all synapses in the caudate nucleus are axo-spinous type IV synapses with a curved and divided asymmetric contact. This strongly suggests that the caudate nucleus interneuronal apparatus is dominated by centre-median input, in contras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1

Year Published

1979
1979
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(27 citation statements)
references
References 22 publications
4
22
1
Order By: Relevance
“…Other studies have compared High and Low VCM rats as far as neuronal spine size and density. In the mammalian striatum the most prevalent neuronal subtype is the medium spiny projection neuron and the majority of striatal synapses are formed with these spines (Chung, Hassler, & Wagner, 1977;Hassler, Chung, Rinne, & Wagner, 1978;Kemp & Powell, 1971a, 1971bRoberts, Gaither, Peretti, Lapidus, & Chute, 1996). Thus, changes in spine size or density could have profound effects on striatal synaptic organization.…”
Section: Previous Morphological Studiesmentioning
confidence: 99%
“…Other studies have compared High and Low VCM rats as far as neuronal spine size and density. In the mammalian striatum the most prevalent neuronal subtype is the medium spiny projection neuron and the majority of striatal synapses are formed with these spines (Chung, Hassler, & Wagner, 1977;Hassler, Chung, Rinne, & Wagner, 1978;Kemp & Powell, 1971a, 1971bRoberts, Gaither, Peretti, Lapidus, & Chute, 1996). Thus, changes in spine size or density could have profound effects on striatal synaptic organization.…”
Section: Previous Morphological Studiesmentioning
confidence: 99%
“…The distribution of glutamate-i was analyzed using SIGMA-SCAN software to quantify the number of colloidal gold particles per square micron in the following profiles: axon terminals forming asymmetric synapses; axon terminals forming symmetric synapses; astrocytic processes; dendrites and the lumen of capillaries. Axon terminals forming asymmetric synapses were not subdivided according to subtypes of Hassler et al (1978). Gold particle density values do not include mitochondrial labeling.…”
Section: Localization Of Glutamate Using Postembedding Techniquesmentioning
confidence: 99%
“…However, the synaptic sites and the precise structures of dopaminergic nerve endings are still uncertain (KAWANA et al, 1971;IMAMOTO and SHIMIZU, 1977). After interruption of the corticostriatal and thalamostriatal connections, dark degeneration features were recognized in the boutons of axo-dendritic and axo-spinous synapses (KEMP, 1968;KEMP and POWELL, 1970;HASSLER et al, 1978). Due to those data the synaptic sites of the nigro-neostriatal projections may be excluded from the above-mentioned synaptic regions, though ARLUISON and collaborators (1978a, b) neglected the synaptic sites and concluded that dopaminergic endings mainly form asymmetric synapses containing small crowded vesicles.…”
Section: Even Immediately After the Multiple Injectionsmentioning
confidence: 99%